General and Specific Mechanisms of Visual Cognitive Function Impairment in People with FMRP Deficit - Pereverzeva, D S; Danilina, K K; Gorbachevskaya, N L (Zurnal vyss̆ej nervnoj dejatelnosti imeni I P Pavlova, 2015)
The purpose of this article is to provide the overview of visual cognitive development in subjects with FMRP deficit. Description of fragile X mental retardation syndrome is presented in the article, that is the most common cause of inherited intellectual disability and one of the most prevalent genetic causes of autism spectrum disorder. The syndrome is associated with deficit of fragile X mental retardation protein following FMR1-gene mutation. Researches of static and dynamic object perception, face perception and oculomotor control are discussed in the article. The results obtained by subjects with FX syndrome are compared with ASD data, syndrome with closed behavioral phenotype. Several factors that underlie visual cognitive deficit are discussed in the article.